THE EFFECT OF USING RUBRICS-BASED INSTRUCTION ON IMPROVING ROBOTICS SKILLS AND ACADEMIC SELF-REGULATION FOR MIDDLE SCHOOL ARAB STUDENTS IN JERUSALEM - Yousef, Ahmad (An-Najah National University, 2024)
This study examined the effects of using Rubric-Based Instruction (RBI) on robotics skills and academic self-regulation among Arab middle school students (ages 12-14) in Jerusalem, addressing educational disparities. This research was based on a true experimental design, comprising 96 students (32 per group) who were randomly allocated to one of three groups: group A received rubric with explanations; group B received rubric but without explanations; and group C was a control group, received conventional instruction -no rubric-. The intervention occurred over eight weeks in an after-school robotics course during Fall 2023. Robotics skills were assessed using validated rubrics, while academic self-regulation was measured using the Self-Regulation Questionnaire-Academic (SRQ-A). Analysis of variance (ANOVA) with Planned Contrast Analyses (PCA) revealed significant differences among groups. For robotics skills, group A significantly outperformed both groups B and C in designing (η² = 0.420) and programming (η² = 0.605) skills. In terms of academic self-regulation, both experimental groups demonstrated significantly lower levels of external regulation, and higher levels of intrinsic motivation compared to the control group. The Relative Autonomy Index (RAI) showed the largest effect, with group A scoring significantly higher than groups B and C. These results demonstrate the effectiveness of using RBI, particularly with detailed explanations, in enhancing robotics skills and fostering more autonomous forms of academic self-regulation in Science, Technology, Engineering, and Mathematics (STEM) education, with important implications for educational policies and practices in culturally similar contexts.
أثر استخدام التدريس المبني على معايير التقييم في تحسين مهارات الروبوتات والتنظيم الذاتي الأكاديمي لدى طلبة المدارس الاعدادية العرب في القدس